Effectiveness of five different approaches in management of urinary tract infection: randomised controlled trial. (5th February 2010) - Little, P; Moore, M V; Turner, S; Rumsby, K; Warner, G; Lowes, J A; Smith, H; Hawke, C; Leydon, G; Arscott, A; Turner, D; Mullee, M
Abstract : Objective To assess the impact of different management strategies in urinary tract infections. Design Randomised controlled trial. Setting Primary care. Participants 309 non-pregnant women aged 18-70 presenting with suspected urinary tract infection. Intervention Patients were randomised to five management approaches: empirical antibiotics; empirical delayed (by 48 hours) antibiotics; or targeted antibiotics based on a symptom score (two or more of urine cloudiness, urine smell, nocturia, or dysuria), a dipstick result (nitrite or both leucocytes and blood), or a positive result on midstream urine analysis. Self help advice was controlled in each group. Main outcome measures Symptom severity (days 2 to 4) and duration, and use of antibiotics. Results Patients had 3.5 days of moderately bad symptoms if they took antibiotics immediately. There were no significant differences in duration or severity of symptoms (mean frequency of symptoms on a 0 to 6 scale: immediate antibiotics 2.15, midstream urine 2.08, dipstick 1.74, symptom score 1.77, delayed antibiotics 2.11; likelihood ratio test for the five groups P=0.177). There were differences in antibiotic use (immediate antibiotics 97%, midstream urine 81%, dipstick 80%, symptom score 90%, delayed antibiotics 77%; P=0.011) and in sending midstream urine samples (immediate antibiotics 23%, midstream urine 89%, dipstick 36%, symptom score 33%, delayed antibiotics 15%; P<0.001). Patients who waited at least 48 hours to start taking antibiotics reconsulted less (hazard ratio 0.57 (95% confidence interval 0.36 to 0.89), P=0.014) but on average had symptoms for 37% longer than those taking immediate antibiotics (incident rate ratio 1.37 (1.11 to 1.68), P=0.003), particularly the midstream urine group (73% longer, 22% to 140%; none of the other groups had more than 22% longer duration). Conclusion All management strategies achieve similar symptom control. There is no advantage in routinely sending midstream urine samples for testing, and antibiotics targeted with dipstick tests with a delayed prescription as backup, or empirical delayed prescription, can help to reduce antibiotic use. Study registration National Research Register N0484094184 ISRCTN: 03525333.